The effect of Virtual Reality in reducing preoperative anxiety in patients prior to arthroscopic knee surgery: A randomised controlled trial - Robertson, A.; Khan, R.; Fick, Daniel; Robertson, William; Gunaratne, D.; Yapa, S.; Bowden, V.; Hoffman, H.; Rajan, R. (IEEE, 2017)
© 2017 IEEE. Preoperative anxiety positively correlates with postoperative levels of pain, analgesic use and length of hospital stay. This preliminary study aimed to determine if the principle of distraction, using a relaxing Virtual Reality (VR) immersion, would reduce preoperative anxiety in patients undergoing arthroscopic knee surgery. Sixty patients were randomised into three groups (Standard care group, Virtual Reality group and iPad group). Anxiety scores (Hospital Anxiety and Depression Scale), Galvanic Skin Response (GSR), heart rate and blood pressure were measured pre and post intervention. The Standard care group received no intervention. The iPad group watched a video slideshow of beaches around the world and the VR group experienced a virtual beach immersion. Guided relaxation audio content (via headphones) was replicated across VR and iPad groups. Planned comparisons showed a significant difference between the average GSR measures at Time 1 and Time 2 between the Standard group and VR group. GSR measures for the Standard care group increased by 54 per cent from time 1 to time 2 and the VR and iPad groups reduced slightly, demonstrating an ameliorating effect on anxiety levels. A marginal difference between the Standard care group and VR group in anxiety change scores was reported. Whilst the VR condition reduced anxiety more than Standard care in both GSR and Anxiety change score measures, it provided no significant advantage over iPad condition. In conclusion, distraction using VR and iPad temporarily reduces self-reported anxiety levels and GSR measures compared to standard care in patients prior to knee arthroscopy. Further study is required to determine how long-lasting these benefits are in a clinical setting. The continuing advancements in VR technology, including immersion quality, present an opportunity to investigate the application of VR as a 'digital pre-med'.